Investigations of Burial Diagenesis in Carbonate Hydrocarbon Reservoir Rocks - Machel, Hans (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2005)
SUMMARY Investigations of burial diagenesis are instrumental for hydrocarbon exploration and exploitation. A proper investigation of diagenesis, with the aim to assist in exploration for and exploitation of hydrocarbons, should follow the "6 -Step Process". Step 1 : facies analysis (including establishing the primary porosity and permeability distributions, and the "primary aquastratigraphy" - a term newly defined in this article); Step 2 : petrographic analyses (paragenetic sequence, mapping amounts and spatial distribution of diagenetic phases); Step 3 : geochemical analyses (isotopes, trace elements, fluid inclusions, etc.); Step 4 : burial history and paleohydrology; Step 5: integration with extant data (especially petrophysical data), if available, and Step 6 : modeling (not necessary, but desirable in at least some cases). Diagenesis, at any depth from near-zero to several kilometres, is governed by various intrinsic and extrinsic factors that include thermodynamic and kinetic constraints, as well as microstructural factors. These factors govern diagenetic processes such as cementation, dissolution, compaction, recrystallization, replacement, and sulfate-hydrocarbon redox-reactions. Cementation, dissolution, and dolomitization require significant flow of groundwater (of whatever type and/or salinity, ranging from fresh to hypersaline), driven by an externally imposed hydraulic gradient. Other processes, such as stylolitization and thermochemical sulfate reduction, commonly take place without significant groundwater flow in hydrologically stagnant systems that are geochemically closed. Two effects of diagenesis that are especially important for hydrocarbon reservoirs are enhancement and/or reduction of porosity and permeability. However, these rock properties can also remain essentially unchanged through diagenesis at depths from near-zero to several kilometres. In extreme cases, an aquifer or hydrocarbon reservoir rock can have highly enhanced porosity and permeability because of extensive mineral dissolution, or it can be plugged up by extensive mineral precipitation.